2005
DOI: 10.1103/physrevd.72.025015
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric dark-matter Q-balls and their interactions in matter

Abstract: Supersymmetric extensions of the Standard Model contain non-topological solitons, Q-balls, which can be stable and can be a form of cosmological dark matter. Understanding the interaction of SUSY Q-balls with matter fermions is important for both astrophysical limits and laboratory searches for these dark matter candidates. We show that a baryon scattering off a baryonic SUSY Q-ball can convert into its antiparticle with a high probability, while the baryon number of the Q-ball is increased by two units. For a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…[8] in connection with astrophysical limits on Q-ball dark matter. However, it was recently shown [9] that the rate of this process is considerably higher than that used in Ref. [8].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…[8] in connection with astrophysical limits on Q-ball dark matter. However, it was recently shown [9] that the rate of this process is considerably higher than that used in Ref. [8].…”
Section: Introductionmentioning
confidence: 77%
“…In a previous paper [9] we reanalyzed the interaction of Q-balls with ordinary matter. We found that quarks falling on a Q-ball are reflected as antiquarks with a probability of order one, practically independent of the parameters of the theory.…”
Section: Interactions Of Susy Q-balls With Mattermentioning
confidence: 99%
“…The solitons found in the simulation might be extremely long lived, serving as dark matter candidates [74] 12 or they might decay into dark matter [75]. The inhomogeneous annihilation, if it is inefficient might lead to signatures during big bang nucleosynthesis or in the late Universe [76].…”
Section: A Additional Observational Consequencesmentioning
confidence: 99%
“…The addition of this coupling modifies the criterions of Q-Ball stability since they can now produce fermions. This fact will have an important interest for cosmology since Q-Balls can play the role of dark matter [5,6]. Particle production from the Q-Ball will reduce its charge Q and at a certain point the Q-Ball will become unstable versus decay into scalars to finally disappear.…”
Section: Introductionmentioning
confidence: 99%